Effect of the characteristics of pores and solid lubricant on the tribological behaviour of sintered steel impregnated with graphite - Araya Rivera, Nicolás Ignacio (2020)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência e Engenharia de Materiais, Florianópolis, 2020.